Anticancer effect of artonin E and chaplashin from artocarpus species on breast cancer cells, MDA-MB-231 and MCF-7 - Ling, Choo Yen (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Breast cancer appears to be a major global health problem. The most common treatment approach of this disease is chemotherapy. However, studies showed that long-term use lead to drug resistance and implies side effect that may cause several genetic alteration, such as gene mutation, DNA methylation and histone modification. Epidemiologic studies revealed that consuming flavonoid rich fruits and vegetables might reduce all types of cancer incidences including breast cancer. Therefore, this research was conducted to evaluate the anticancer effect of two types of flavonoid extracted from Artocarpus sp, Artonin E and Chaplashin towards breast determine anticancer effect of Artonin E and Chaplashin towards MDA-MB-231 and MCF-7 breast cancer cell lines and to determine mode of cell death of cells treated with most potent compound by assessing nuclear fragmentation effect. Dose-dependent inhibitory effect of cell growth on MDA-MB-231 and MCF-7 breast cancer cells with a median inhibition concentration (IC50) was determined by methylene blue assay. The IC50 concentration was then used to analyse nuclear fragmentation event using fluorescence dye Hoeschst 33342. Mode of cell death was confirmed by flow cytometry analysis using Annexin-V/PI double staining. It was found that Artonin E showed better anticancer activity towards MDA-MB-231 cells with IC50 of 4.95 pg/ml compared to Cisplatin with IC50 of 5.88 pg/ml. Chaplashin showed the best activity towards MDA-MB-231 breast cancer cells with IC50 of 24.80 pg/ml. Nuclear fragmentation assay showed the cells treated with Artonin E absorbed more distinct fluorescent blue glow compared to the untreated cells. The stained morphology indicated apoptosis characteristic as nuclear fragmentation appeared clearly in the treated cells. Thus, we postulated that anticancer effect in the treated cells underwent apoptosis. In conclusion, Artonin E exerted strong antipoliferative effects to attribute anticancer effect potential towards MDA-MB-231. Mode of cell death confirmed the induction of apoptosis when nuclear fragmentation occurred in the treated cancer cells. Therefore, these plant-derived compounds need further investigation to support the anticancer effect. Thus it might become a potential anticancer drug in the future.